The Contextual, Stylistic, and Social Specificity of the Usage of ChatGPT Terms in English and Uzbek Languages - Normamatova Zakhro Dilshodovna (Scientific Trends, 2025)
The rapid advancement of artificial intelligence (AI), particularly in natural language processing (NLP), has introduced new terminologies that permeate global communication networks. ChatGPT, a state-of-the-art AI language model developed by OpenAI, has generated a new lexicon used differently across languages and cultures. This study investigates the contextual, stylistic, and social specificities in the use of ChatGPT-related terms in English and Uzbek languages. Through a comparative linguistic analysis supported by corpus data and sociolinguistic methodology, we explore how cultural factors, language structure, and social context influence the adoption, adaptation, and usage of these terms. Findings reveal unique patterns in stylistic registers and context-dependent meanings, reflecting broader sociocultural dynamics and language contact phenomena. The study contributes to emerging research fields at the intersection of AI linguistics, bilingual term usage, and cross-cultural communication.
Keywords: ChatGPT terminology, English language, Uzbek language, contextual usage, stylistic variation, sociolinguistics, AI linguistics, bilingual lexicon, language adaptation, language contact.